2008
DOI: 10.1111/j.1600-0501.2008.01534.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of local and systemic factors on the incidence of late oral implant loss

Abstract: Implant location in the oral cavity and radiotherapy seem predominant to explain the occurrence of implant loss. On the other hand, smoking and systemic health factors do not seem to be prominent players in the etiology of late implant loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
235
3
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(292 citation statements)
references
References 29 publications
18
235
3
10
Order By: Relevance
“…16 The authors found no significant differences in late failure between normal and hypertensive individuals. 16 However, the impact of hypertension on early implant failures rate, which is directly related to the wound healing process in the early stage of osseointegration, has never been tested.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…16 The authors found no significant differences in late failure between normal and hypertensive individuals. 16 However, the impact of hypertension on early implant failures rate, which is directly related to the wound healing process in the early stage of osseointegration, has never been tested.…”
Section: Introductionmentioning
confidence: 79%
“…8,9 Although the hypothesis that hypertension may have a harmful effect on bone density was previously evaluated in a series of animal and clinical studies, [10][11][12][13][14] to date, few investigations have focused on the influence of hypertension on bone healing. 15 Currently the hypothesis that the hypertension could lead to an increased incidence of late implant loss was evaluated by Alsaadi et al (2008). 16 The authors found no significant differences in late failure between normal and hypertensive individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The meta-analysis included 7 controlled clinical trials (Morris et al, 2000;van Steenberghe et al, 2002;Dowell et al, 2007;Alsaadi et al, 2008a;Tawil et al, 2008;Levin et al, 2011;Grandi et al, 2013) and 7 retrospective analyses (Keller et al, 1999;Accursi, 2000;Doyle et al, 2007;Alsaadi et al, 2008b;Anner et al, 2010;Bell et al, 2011;Le et al, 2013). The study of Grandi et al (2013) was a randomized clinical trial for immediately vs. early loaded implants but not for diabetic vs. non-diabetic patients.…”
Section: Description Of the Studiesmentioning
confidence: 99%
“…Treatment success versus failure factors include the biomechanical condition, the microbial environment, and the host bone quality and quantity [2]. The latter factor is closely associated with systemic diseases associated with ageing, such as osteoporosis and diabetes.…”
Section: Introductionmentioning
confidence: 99%